THE OLD CHURCH SLAVONIC VICES FROM THE ETYMOLOGICAL POINT OF VIEW: THE GLUTTONY - Janyskova, Ilona (Bohemica Olomucensia, 2020)
The article deals with the Old Church Slavonic / Church Slavonic words with the meaning of 'gluttony (i.e. intemperance in eating and drinking)' contained in the Dictionary of the Old Church Slavonic Language, and provides their etymology. In particular, these are the words obedanije, obedenije, jadь, lichaja jadь, the composite lichojadenije 'intemperance in eating', pijanьstvo, pijanьstvije, the composite lichopitije 'intemperance in drinking', other lexemes and interesting connections closely related to this topic are also listed.
Keywords: slavistics; etymology; semantics; Old Church Slavonic; gluttony